2017
DOI: 10.1039/c7cp03729e
|View full text |Cite
|
Sign up to set email alerts
|

The role of van der Waals and exchange interactions in high-pressure solid hydrogen

Abstract: We investigate the van der Waals interactions in solid molecular hydrogen structures. We calculate enthalpy and the Gibbs free energy to obtain zero and finite temperature phase diagrams, respectively. We employ density functional theory (DFT) to calculate the electronic structure and Density functional perturbation theory (DFPT) with van der Waals (vdW) functionals to obtain phonon spectra. We focus on the solid molecular C2/c, Cmca-12, P 6 3 /m, Cmca, and P bcn structures within the pressure range of 200 < P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…Experimentally, no metallic phases have been observed in this pressure range, and quantum nuclear effects do not account for this discrepancy either. 4 The too low metallisation pressure can be attributed to the lacking of van der Waals interactions in PBE functional, 40 resulting in underestimation of the stability in the molecular structures. We note that Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, no metallic phases have been observed in this pressure range, and quantum nuclear effects do not account for this discrepancy either. 4 The too low metallisation pressure can be attributed to the lacking of van der Waals interactions in PBE functional, 40 resulting in underestimation of the stability in the molecular structures. We note that Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9]13,[36][37][38][39] However, different parameterisations of the XC functional in DFT give inconsistent predictions, e.g., PBE predicts a too low metallisation pressure compared with experiments, whilst other exchange functionals produce higher pressures than DMC. 4,35,40 Instead, more accurate methods including diffusion Monte Carlo (DMC) have been employed to predict more reliable pressure temperature-phase diagrams, [2][3][4]31,32 which correct the underestimation of the metallisation pressure by DFT-PBE to a large extent. However, DMC calculations rely on the fixed-node approximation, and most of the current studies use crystal structures optimised using DFT.…”
Section: Introductionmentioning
confidence: 99%
“…The metalization of hydrogen has been seen as a compelling subject of study by many scientists, ranging from experimental chemists and physicists [134,135,136,137,10,463,9], to theoreticians [139,140,141]. However, despite the great advancement in high pressure-techniques and tools, the metalization of hydrogen in its solid phase has proven to be very challenging, and still debated [142,143,144,145,146,147,148,149,150,151,152]. The P − T phase diagram of hydrogen comprises many structures, including solid and molecular crystals and is so complex that it could be subject of a Review by itself [463].…”
Section: Elemental Hydrogen At Hpmentioning
confidence: 99%
“…The choice of exchange correlation functional is a highly debated topic in DFT studies of hydrogen. In a benchmarking studies on hydrogen the BLYP functional 22,23 was shown to give results closest to Quantum Monte Carlo calculations 24,25 , for transition pressures and vibrational frequencies, due mainly to the correct asymptotic behaviour at high charge density gradient 26 .…”
Section: Methodsmentioning
confidence: 94%
“…Furthermore, the hydrogen structure is the same in all compounds at the same lattice parameter, while the intermolecular distances within the supermolecule are highly dependent on density. Explicit treatment of van der Waals interactions is critical at low densities in hydrogen, but of secondary importance at pressure 26 . Here van der Waals interactions modelled by the Tkatchenko-Scheffler correction to PBE produced the same structures, further evidence that packing via the P V term in the enthalpy is more important.…”
Section: Discussionmentioning
confidence: 99%